Tamarack County : a novel - Krueger, William Kent (Krueger, William Kent. Cork O'Connor mystery., 2013)
Faced with a series of dark occurrences that are linked to a twenty-year-old murder, private investigator Cork O' Connor must stop a vengeful force before his family and friends pay the ultimate price.